The Impact of Social Media Marketing, Reviews and Fear of Missing Out on Purchase Intention - Mauliya Tahta Septia; Moh. Agung Surianto (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The rapid development of digital technology has brought major changes in consumer behavior, especially in online shopping activities through e-commerce platforms. East Java is one of the potential markets with the dominance of platforms that are in high demand such as Shopee. This study aims to analyze the influence of Social Media Marketing, Online Customer Review, and Fear of Missing Out on consumer purchase intention on the Shopee platform in the region. With a quantitative approach and explanatory research design, data was collected through an online questionnaire based on the Likert scale which was randomly distributed through social media. The purposive sampling technique is used to ensure that respondents are active Shopee users in a certain age category. Data analysis was carried out using the multiple linear regression method with validity, reliability, and classical assumption testing. The results of the study show that the three independent variables have a significant influence on consumer purchase intention, both partially and simultaneously. Social Media Marketing plays a role through engaging and interactive content, while Online Customer Reviews contribute to building trust through credible and relevant reviews.